2009
DOI: 10.1016/j.joca.2009.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Surface topography of viable articular cartilage measured with scanning white light interferometry

Abstract: The aim of developing a protocol based on white light interferometry to measure the surface topography of viable articular cartilage was achieved. This interferometric technique opens the door to monitoring the surface topography of live cartilage, as is desirable for ex vivo tests on cartilage explants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 25 publications
1
31
0
Order By: Relevance
“…Half of the dissected sample was fixed in formalin, processed for paraffin embedding, sliced to a thickness of 5 µm, and exposed to deparaffinization washes in xylene and decreasing concentrations of alcohol. Slides were stained with Safranin-O/fast green to evaluate the presence of matrix proteoglycans 34 and imaged with 4× and 10× objectives. Morphology was assessed using previously reported modified scoring criteria, 35 originally established by Mankin and Lippiello.…”
Section: Tissue Analysis: Tissue Loss Histology and Viabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Half of the dissected sample was fixed in formalin, processed for paraffin embedding, sliced to a thickness of 5 µm, and exposed to deparaffinization washes in xylene and decreasing concentrations of alcohol. Slides were stained with Safranin-O/fast green to evaluate the presence of matrix proteoglycans 34 and imaged with 4× and 10× objectives. Morphology was assessed using previously reported modified scoring criteria, 35 originally established by Mankin and Lippiello.…”
Section: Tissue Analysis: Tissue Loss Histology and Viabilitymentioning
confidence: 99%
“…With a commercially available live/dead staining kit, samples were incubated in phosphate-buffered saline containing calcein AM and ethidium homodimer-1 for 45 minutes at 37°C (Invitrogen Molecular Probes, Eugene, OR). 34 Samples were imaged using a fluorescence-light microscope (Eclipse TE2000-S; Nikon Instruments Inc., New York, NY), charge-coupled device (CCD) camera (SPOT RT-KE Color 3-Shot, Model 7.3x; Diagnostic Instruments, Sterling Heights, MI) and 5× objective.…”
Section: Tissue Analysis: Tissue Loss Histology and Viabilitymentioning
confidence: 99%
“…Reported surface roughness data of healthy and osteoarthritic cartilage surfaces exhibited differences in these studies. For instance, the measurements showed that the mean surface roughness values of smooth, intermediate, and rough cartilage samples were 7.973.3, 29.177.8 and 49.1 μm, respectively, when using high frequency ultrasound [54], while using scanning white light interferometry, the average surface roughness values of human cartilage samples in OA grades 0, 1 and 2 were 0.8070.3, 1.070.3 and 1.7070.9 μm, respectively [56]. Surface roughness was reported to be 30 μm for a healthy condyle with a smooth surface [55].…”
Section: Surface Morphological Properties Of Articular Cartilage and mentioning
confidence: 98%
“…Cartilage surface alterations of animal samples were investigated at a micrometer scale using high frequency ultrasound [54], optical profilometry [55], scanning white light interferometry [56], and laser scanning confocal microscopy (LSCM) [57,58]. Graindorge et al found that changes occurred in the surface morphology of the articular cartilage of sheep leg during wear [38].…”
Section: Surface Morphological Properties Of Articular Cartilage and mentioning
confidence: 99%
“…Prior to measurements, the surface was blotted with low lint wipes, sprayed with canned air for 5 s, and air dried for 1-2 min at room temperature in order to avoid interference of discrete fluid films with the interferometry measurements. 22 After testing, Indian ink was used to visualize the damaged cartilage tissue on the articular surface and imaged with a dissection microscope (Nikon SM2800; Melville, NY). The areas that were stained after wiping the surface with a damp cloth indicated damage based on the adherence of Indian ink to fibrillated cartilage, and were assessed with a semi-quantitative analysis.…”
Section: Wear Assessmentmentioning
confidence: 99%